(untitled) (Research, Society and Development, 2020)
The hegemonic development in the field, which today is defined by the ideological matrix of agribusiness, is based mainly on monoculture and the use of pesticides, with the objective of increasing food production with the discourse of meeting the demand for the world population. However, several problems arose due to this logic of production, such as irreversible damage to the environment, problems in human health, losses in the field, food waste, among others. Considering this context, reflections, discussions and actions aimed at the conservation of the environment are growing in society, and an important tool for raising awareness in favor of the rational use of resources present in nature is Environmental Education. Through this, it is possible to provide the articulation between different areas of knowledge, in order to take knowledge and reflections, present experiences and raise awareness about the need to preserve, conserve and recover areas, among many other aspects related to the relationship established between human beings and the nature. In this perspective, this article aimed to analyze how Environmental Education can contribute to the promotion of healthy eating, pointing out the reflexes of the food production process in sustainable development. Thus, a literature review on Food Education and Healthy Eating was carried out. The results of the studies were analyzed, providing a synthesis on the subject in question. It was found that some authors point to the success of Environmental Education as an instrument to sensitize people to an ecological spirit, therefore, it is an important instrument in an attempt to minimize the negative impacts resulting from food.